ANALISIS BEBAN KERJA FISIK DENGAN KELELAHAN KERJA PETANI GAPOKTAN DI DEMANGAN PONOROGO - Aisy Rahmania (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2022)
The physical workload is one of the factors that could trigger excessive work fatigue. This study aimed to analyze the correlation between physical workload and work fatigue among Gapoktan farmers in Demangan Village Ponorogo. The type of research is an analytical quantitative with a cross-sectional approach. The population is 150 farmers with a sample of 60 respondents using the accidental sampling technique. The instruments used are an oximeter to measure physical workload and IFRC Questionnaire to measure work fatigue. This study shows a correlation between physical workload and work fatigue among Gapoktan farmers in Demangan Village Ponorogo with a p-value = 0.025 (< 0.05) with the value of the correlation shown by the number 0.289, which means it has a low correlation strength. The conclusion of this study is that there is a significant correlation between physical workload and work fatigue on Gapoktan Farmers in Demangan Village Ponorogo. The advice given to the farmers community is to regulate working hours and rest hours so that they do not have excessive physical workloads or work fatigue. Another way to avoid excessive workload and work fatigue is to adopt a healthy lifestyle.